2019
DOI: 10.4102/sajcd.v66i1.615
|View full text |Cite
|
Sign up to set email alerts
|

Community service speech language therapists practising in adult dysphagia: Is the healthcare system failing them?

Abstract: Performing community service is a necessity prior to practising speech language therapy in South Africa. This system allows for improved access to these specialised services in the more rural areas. The current challenges of practising in complex settings with little access to mentorship can result in these community service therapists feeling underprepared to assess and manage patients presenting with adult dysphagia (swallowing disorders). This paper explores this topic through the theoretical lens of decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…It is thus concerning that for patients with dysphagia, therapeutic interventions were relatively infrequently recommended, and that dysphagia-specific interventions were not recommended at all for at least 9.29% of patients with dysphagia. Studies have found that newly graduated SLTs in South Africa lack confidence and feel unprepared with regard to dysphagia management (Singh et al, 2015 ; Yiannopoulos, 2016, as cited in Coutts, 2019 ), which may underlie a more conservative approach to dysphagia management in recommending enteral nutrition over other interventions. This likely impacts on outcomes and quality of life of patients presenting with dysphagia and suggests a need for further undergraduate training on the management thereof, as well as access to clinical supervision and evaluation in this area of practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus concerning that for patients with dysphagia, therapeutic interventions were relatively infrequently recommended, and that dysphagia-specific interventions were not recommended at all for at least 9.29% of patients with dysphagia. Studies have found that newly graduated SLTs in South Africa lack confidence and feel unprepared with regard to dysphagia management (Singh et al, 2015 ; Yiannopoulos, 2016, as cited in Coutts, 2019 ), which may underlie a more conservative approach to dysphagia management in recommending enteral nutrition over other interventions. This likely impacts on outcomes and quality of life of patients presenting with dysphagia and suggests a need for further undergraduate training on the management thereof, as well as access to clinical supervision and evaluation in this area of practice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the relationship between the number of days from admission to referral and the number of SLT sessions was not significant. However, it is well known that public-sector hospitals in South Africa are challenged by limited physical and human resources (Andrews & Pillay, 2017;Coutts, 2019), and hospital capacity and pressure for beds have both been documented as reasons for premature hospital discharge locally and internationally (Dreyer & Viljoen, 2019;Glette, Kringeland, Røise, & Wiig, 2019). For this reason, the possibility of earlier hospital discharge based on medical stability, regardless of the need for continued inpatient rehabilitation, should not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This raised an interesting point as the relationship between colleagues may then have a role to play in this learning and/or mentoring process. This highlights the importance of placing junior SLTs in facilities where they can be mentored by more experienced SLTs in dysphagia, as this is a valuable learning opportunity (Coutts, 2019).…”
Section: The Speech-language Therapist Factors: How It Is All Pulled Togethermentioning
confidence: 99%
“…One of the participants summed it up well and supports the use of the term 'clinical instincts' when she said, 'It made me realise how much of my decision-making is unspoken and based on very subtle things … it was difficult to explain those subtleties…'. This is important when considering undergraduate teaching, as well as mentorship for junior SLTs as they proceed into their community service year (Coutts, 2019). As shown in the table, clinical instincts are a predominant feature of critical thinking, and needs to be nurtured and developed from junior years.…”
Section: The Speech-language Therapist Factors: How It Is All Pulled Togethermentioning
confidence: 99%
See 1 more Smart Citation